On the Composition of the Distributions x^λ _+ ^m x_+ and x_+^-1/λ - Fisher, B.; Kraiweeradechachai, T. (Sarajevo Journal of Mathematics, 2024)
Let F be a distribution and let f be a locally summable... 2000 Mathematics Subject Classification. 46F10